Cardiovascular disease in pregnancy - Vyas, Rupa; Gupta, Priya; Shah, Sapana; Rangoliya, Komal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Maternal cardiac disease is a major cause of non-obstetric maternal morbidity and mortality. The care of pregnant women with cardiac disease requires a multidisciplinary approach, involving obstetricians, cardiologists and anesthesiologist. Methods: A prospective analytical study of maternal heart disease and its fetomaternal outcome is carried out in the department of obstetrics and gynecology at tertiary hospital and teaching institute. The study was carried out on 50 cases belonging to age group 18-50 years with various cardiac diseases during their pregnancy and peripartum period. Results: In this study, 78% of the cases were registered with our hospital. The present study shows about 32% of the women having cardiac disease were in the age group of 20-25 years. 34% belonged to NYHA class II and had a relatively uneventful peripartum period. Among all forms of heart disease, RHD was common constituting 26% of cases. Most common condition associated with cardiac disease in pregnancy was preeclampsia (36%) in our study, with anemia being other one (10%). The common complications were congestive cardiac failure (12%) and pulmonary edema (8%). Combination of diuretics and beta blockers was used most commonly (22%). 56% of women delivered with caesarean section. 42 patients delivered after age of viability with 29 (69%) term deliveries and 13 (30%) preterm deliveries with 8 requiring NICU care. Conclusions: Valvular heart disease of rheumatic origin is the most common cardiac disease associated with pregnancy.The availability of adequate systems of early diagnosis of cardiac lesion, reference to tertiary care center & close monitoring of patient and delivery with multidisciplinary approach include specialized cardiologic care, high risk obstetric support and neonatology expertise that can minimize the serious consequences and helps to improve fetomaternal outcome. Pre-conceptional counseling and surgical correction of certain conditions improves maternal as well as fetal outcome. Awareness needs to be created about heart diseases during pregnancy and the importance of regular antenatal check-ups.